Quantification of hydroperoxides by gas chromatography‐flame ionization detection and predicted response factors. (1st May 2016) - Leocata, Sabine; Frank, Sandy; Wang, Ying; Calandra, Michael J.; Chaintreau, Alain
Abstract: The quantification of hydroperoxides is crucial in several areas, in particular in the fragrance domain, because they have been identified as skin sensitizers. The reference compounds necessary to calibrate the instruments have very limited availability, and require drastic storage conditions (‐78 °C) due to their instability. To overcome these limitations, we propose a GC‐FID approach involving their silylation, and the prediction of response factors. This procedure provides a good alternative to a full calibration down to a concentration level of 500 mg/kg, with an underestimation of about 20%. In the analysis of essential oils and fragrance concentrates, larger deviations are found; however, they are not inherent in the technique but rather in the chemistry of hydroperoxides that readily react with aldehydes to form peroxyhemiacetals, thereby decreasing the concentration of free hydroperoxides. These observations are in agreement with quantitative 1 H NMR and HPLC‐Chemiluminescence analyses. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : To quantify the hydroperoxides, we propose a GC‐FID approach involving their silylation, and the prediction of their response factors to avoid the use of unstable calibration standards. It provides a good alternative to a full calibration down to a concentration level of 500 mg/kg, with an underestimation of about 20%. In the analysis of essential oils and fragrance concentrates, larger deviations are observed due to the reaction of hydroperoxides with aldehydes to form peroxyhemiacetals, thereby decreasing the concentration of free hydroperoxides. These observations are in agreement with quantitative 1 H NMR and HPLC‐Chemiluminescence analyses.